PELAYANAN PEMBUATAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUANTAN SINGINGI - Randi Novrizal; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The Government of the Republic of Indonesia has basic functions, namely as empowerment, development and services. One of the functions of government as a service is to provide services for identity and citizenship rights. This study aims to determine how services and supporting factors as well as constraints in the service of making birth certificates at the Department of Population and Civil Registration of Kuantan Singingi Regency. The results showed that the service for making birth certificates at the Department of Population and Civil Registration of Kuantan Singingi Regency was seen from the following 6 public service standards: (1) service procedures, simple service procedures and easy to understand by the community; (2) completion time, the completion time is still uncertain; (3) service fees, free costs; (4) service products, service products in accordance with the wishes of the community; (5) incomplete facilities and infrastructure, facilities and infrastructure; (6) Competence of service providers, officers have served in a friendly and fair manner. Service support factors are awareness and regulatory factors. The inhibiting factors are the lack of infrastructure, human resources and lack of public awareness